Providing Managerial Incentives: Cash Flows versus Accrual Accounting - Reichelstein, Stefan (Journal of Accounting Research, 2000)
This paper analyzes a principal-agent model in which the agent (manager) can exert effort in every period in order to gain access to some investment opportunity. He or she then decides whether the firm undertakes the opportunity. My analysis focuses on satisfactory incentive schemes which motivate the manager to exert effort and to invest in all profitable projects. As a consequence, the principal's gross benefit is held fixed, and the variable of interest is the resulting agency cost, i.e., the present value of all compensation payments to the manager. The manager's compensation payments are based on a performance measure chosen by the principal. My analysis compares performance measures based only on realized cash flows with the residual income performance measure. I assume that the calculation of residual income is based on depreciation charges which reflect the useful life of assets as well as the intertemporal distribution of cash flows generated by those assets. For suitably chosen depreciation charges, residual income reflects at each point in time the value currently created by the manager.